Preparation and Microwave Absorption Properties of NixSy/PVDF Nanocomposites - Du, Yu-Hui; Gao, Na; Li, Mao-Dong; Wang, Lei; Wang, Guang-Sheng (Frontiers in Materials, 2020)
Octahedral NixSy nanoparticles and NixSy/PVDF nanocomposites are successfully prepared by solvothermal method. The electromagnetic absorption performance of NixSy/PVDF with different filling concentrations is investigated in the range of 2-18 GHz. An optimal reflection loss value of −32.75 dB at 10.48 GHz is achieved for the filled with concentration of 20 wt%, and the bandwidth less than −10 dB can reach up to 4.48 GHz with a thickness of 3 mm. Furthermore, fundamental mechanisms for absorbing is discussed, it is found that the interface polarization, electric dipole polarization, Debye relaxation and impedance matching are the main factors affecting the absorption performance of NixSy/PVDF.